Defining Clinically Significant Outcomes for Revision Arthroscopic Rotator Cuff Repair (230). Issue 10 (31st October 2021) - Huddleston, Hailey; Polce, Evan; Fu, Michael; Nicholson, Gregory; Forsythe, Brian; Cole, Brian; Verma, Nikhil; Yanke, Adam
Objectives: While clinically significant outcomes including Minimal Clinically Important Difference (MCID), Substantial Clinical Benefit (SCB), and Patient Acceptable Symptom State (PASS) have been defined in primary rotator cuff repair (RCR), these values have not been established in revision RCR. Revision cases may be associated with lower absolute improvement compared to primary cases, and outcomes should therefore be assessed against revision-specific clinically significant differences. The purpose of this study was to define clinically significant outcomes in American Shoulder and Elbow Surgeons (ASES), Single Assessment Numeric Evaluation (SANE), and Constant scores, and to investigate factors associated with achievement of significant improvement following revision arthroscopic RCR. We hypothesized that MCID, SCB, and PASS values would be lower than those reported for primary RCR patients. Methods: A retrospective review of revision RCRs from July 2014 through June 2019 was performed. Patients who did not complete any patient reported outcomes (PROs) and those who underwent superior capsular reconstructions were excluded; graft augmentations were included. MCID was calculated with the distribution-based method, whereas SCB and PASS were calculated using anchor-based methodology from postoperative PRO scores. The SCB was determined by comparing the PRO scores of the substantial improvement and control patient cohorts, and PASS was determined by comparing the PRO scores of patients responding as satisfied and unsatisfied with their postoperative outcome. Receiver operating characteristic (ROC) curves and area under the curve (AUC) analysis were used to calculate optimal threshold scores corresponding to achievement of the SCB and PASS. Optimal thresholds were determined through maximization of sensitivity and specificity via Youden's index. This process was repeated for each questionnaire (ASES, SANE, and Constant). Wilcoxon signed-rank paired tests were used to assess improvement in PRO scores from baseline. Threshold analysis to determine if any preoperative PRO scores were sufficiently predictive of achieving the MCID, SCB, or PASS were performed. Results: A total of 97 patients were identified and 54 patients (51 anchor responses) answered 1-year PROs. All PROs demonstrated significant increases from baseline to 1-year postoperatively (all P < 0.001). There was a gain of 22.4, 19.9, and 5.7 points for ASES, SANE, and Constant from baseline, respectively. MCID was 13.7, 14.1, and 4.2 for ASES, SANE, and Constant, respectively (Table 1 ). Values for SCB using the physical function and pain anchors, and PASS using the satisfaction anchor are demonstrated inTable 1 . For physical function improvement, 26 patients (51.0%) had some degree of improvement, 15 patients (29.4%) had no change or negligible change in their status, and 10 patients (19.6%) were worse based on the anchor question. For the pain anchor, 24 patients (47.1%) had some degree of pain improvement, 16 patients (31.4%) had no change or negligible change in their status, and 11 patients (21.6%) were worse. Preoperative PRO score thresholds that were predictive of achieving MCID, SCB, and PASS are presented inTable 2 . There were no significant effects of sex on attaining any clinically significant outcome, but a greater age was associated with a higher likelihood of achieving SCB (r = 0.299, p = 0.043) on Constant. BMI was negatively correlated with achieving SCB on SANE (r = -0.383, p = 0.009), while WC status was negatively correlated with achievement of SCB (13.3% WC vs 58.9% non-WC, p = 0.005) and PASS (13.3% WC vs 58.9% non-WC, p = 0.029) on SANE. Conclusions: In this study, we defined MCID, SCB, and PASS values at 1-year for ASES, SANE, and Constant in patients undergoing revision RCR. Our MCID values were higher for ASES but lower for SANE and Constant compared to prior studies on clinically significant outcomes in primary RCR. Our findings suggest different clinical thresholds should be used in the revision RCR population.